Meaning in law a theory of speech - Collier, Charles W., 1950- (New York ; Oxford : Oxford University Press, 2009)
Collier develops a general legal theory of speech on the basis of linguistic theory and the philosophy of language. He retraces the main conceptual stages in the expression of meaning, from natural notions of meaningfulness, through symbolism, to signification.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Freedom of expression; Semantics (Law); Law -- Philosophy